Digitization of Cooperatives and the Utilization of Technology to Increase Economic Competitiveness in the Madurese Written Batik Sector (Proceeding of the International Conference on Economics, Accounting, and Taxation, 2024)
Digitization of cooperatives and the use of technology are strategic steps in increasing economic competitiveness in the Madura handwritten batik sector, especially in Central Pakandangan Village, Sumenep Regency. This program aims to empower handwritten batik artisans through technology integration and digital capacity building. Some of the main activities include Search Engine Optimization (SEO) training, digital financial management through Accountable Digital Financial Management, digital cash book preparation, as well as Social Media Officer training and social media management strategies. The participants were also trained to create creative content, carry out digital branding of batik through logo design and visual branding, as well as build digital partnerships and cooperation. In addition, technological innovations are introduced through the use of night blasting machines to support production efficiency. This approach is expected to be able to increase the visibility of Madura written batik products, expand the market, and strengthen the competitiveness of artisans in the digital era. With a combination of training and the application of technology, this program contributes to the transformation of the digital-based economy in the Madura batik sector.